Thiacloprid Induced Developmental Neurotoxicity via ROS-Oxidative Injury and Inflammation in Chicken Embryo: The Possible Attenuating Role of Chicoric and Rosmarinic Acids - Mayada R. Farag; Samah R. Khalil; Asmaa W. Zaglool; Basma M. Hendam; Amr A. Moustafa; Raffaella Cocco; Alessandro Di Cerbo; Mahmoud Alagawany (Biology, 2021)
Insecticides are widely employed in agriculture to control pests and as major factors for enhancing crop productivity. Thiacloprid (TH) is one of the most-used insecticides worldwide. In this study, the negative impact of TH on the brain tissue of developing chicken embryo models and the modulatory effect of chicoric (CA) and rosmarinic (RA) acids were investigated. The eggs were injected in ovo with different doses of TH (0.1, 1, 10, and 100 μg/egg). TH significantly increased the oxidative damage in the brain of exposed embryos in a dose-dependent manner (p < 0.05). TH significantly elevated the oxidative stress markers; protein carbonyl, malondialdehyde content, and DNA damage (p < 0.05). Myeloperoxidase activity and nitric oxide significantly increased with overexpression of the pro-inflammatory cytokines (interferon gamma, tumor necrosis factor alpha, and interleukin-1 beta) and stress-related and apoptotic genes (NF-KB, Caspase-3) in the brain tissue on both biochemical and molecular levels (p < 0.05), while downregulating the expression of antiapoptotic Bcl-2. Co-treatment of CA and RA with TH markedly decreased the insecticide-induced toxicity with a prominent synergistic effect (p < 0.05). In conclusion, TH is suggested to be a possible neurotoxic to embryos of vertebrates including human. The study also revealed the antioxidant, anti-inflammatory, genoprotective, and antiapoptotic property of CA and RA against TH toxicity.